Peran Etnis dan Kultural Pada Persaingan Industri Tahu Takwa di Kota Kediri - Riyan Amiruddin (Universitas Mataram, 2020)
Culture is a life mechanism that is repeated and regenerated in society. Cultural elements also have shaping aspects, one of which is ethnicity. The role of culture in an ethnic context is as a basis for forming thoughts, characters and habits so that it becomes a special identity for an ethnicity. Therefore, this has become a topic in this research and aims to explore issues related to the cultural economy in the context of the competition for the tahu takwa industry in Kediri. Cultural economy is an economic activity that combines in a regenerative articulation of culture. This research is important, because the takwa industry is an icon attached to the city of Kediri and tries to explain the results of cultural economic exploration in the context of 2 Javanese Chinese ethnicities. Various findings of researchers will be presented in this paper regarding the role of tofu commodity as a medium of representation of ethnicity, work ethic and social capital between Javanese and Chinese ethnicities. The research method in this research uses qualitative indepth interview data collection techniques. The results of the research study will present the results of cultural economic exploration covering work ethic, identity, competition patterns, social network market construction and the resilience of the tofu industry in two dimensions between Chinese and Javanese ethnicities.